2016
DOI: 10.1111/eva.12406
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐immunology and bioinvasion: revisiting the evolution of increased competitive ability hypotheses

Abstract: Immunity is at the core of major theories related to invasion biology. Among them, the evolution of increased competitive ability (EICA) and EICA‐refined hypotheses have been used as a reference work. They postulate that the release from pathogens often experienced during invasion should favour a reallocation of resources from (costly) immune defences to beneficial life‐history traits associated with invasive potential. We review studies documenting immune changes during animal invasions. We describe the desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 113 publications
(190 reference statements)
1
41
0
Order By: Relevance
“…More generally, invasive species offer exceptional opportunities as natural experiments to study evolutionary processes that shape the immune system. The role of the immune system as both a target of selection and as a determinant of invasion success is becoming increasingly recognised (Cornet et al., ; Dunn & Perkins, ). Studies on invasive species have identified the dangers of inappropriate autoimmune response or the energetic costs and trade‐offs associated with different defence strategies as potential determinants of invasion success (Brown, Phillips, et al., ; Lee & Klasing, ).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, invasive species offer exceptional opportunities as natural experiments to study evolutionary processes that shape the immune system. The role of the immune system as both a target of selection and as a determinant of invasion success is becoming increasingly recognised (Cornet et al., ; Dunn & Perkins, ). Studies on invasive species have identified the dangers of inappropriate autoimmune response or the energetic costs and trade‐offs associated with different defence strategies as potential determinants of invasion success (Brown, Phillips, et al., ; Lee & Klasing, ).…”
Section: Discussionmentioning
confidence: 99%
“…Such immune responses are also costly due to energetic expenditure (the reduction of nutrients available for partitioning across tissues due to their use in mounting immune responses; Klasing & Leshchinsky, 1999) and to the potential for collateral damage (tissue injury due to the effects of the immune response; Martin et al, 2010). Nonetheless, loss of immunocompetence (the ability to mount a normal immune response after exposure to an antigen; Janeway, Travers, & Walport, 2001) could render invaders susceptible to infection by novel pathogens and parasites in their introduced range (Cornet et al, 2016;Lee & Klasing, 2004). Nonetheless, loss of immunocompetence (the ability to mount a normal immune response after exposure to an antigen; Janeway, Travers, & Walport, 2001) could render invaders susceptible to infection by novel pathogens and parasites in their introduced range (Cornet et al, 2016;Lee & Klasing, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These nests can vary substantially in size and queen productivity (Barlow et al ). The expansion of a species’ range has been associated with changes in immunocompetence (Cornet et al ) and it has been hypothesized that low genetic diversity in social invasive species may affect immune responses on colony and individual level (Ugelvig and Cremer ). Recently, the common wasp has been shown to carry viral pathogens.…”
mentioning
confidence: 99%